The Dilemma of Islamic Rationalism: A Critical Study of Bassam Tibi’s Thought in Modernity - Andri Lupias Satedy (Jurnal Iman dan Spiritualitas, 2026)
This study critically examines Bassam Tibi’s concept of Islamic rationalism within the context of modernity. It aims to explore how Tibi distinguishes between Islam as a universal ethical system and Islamism as a political ideology that often rejects rationality and pluralism. Employing a qualitative, library-based approach with content analysis and critical hermeneutics, the study analyzes Tibi’s major works—especially Islamism and Islam—and related scholarly debates on the relationship between Islam, rationality, and modernity. The findings reveal that Tibi proposes a revival of Islamic rationalism as a response to the epistemological crisis in the Muslim world, yet his framework remains influenced by Eurocentric notions of modernity. Conversely, Muslim thinkers such as Harun Nasution, Nurcholish Madjid, and al-Attas advocate for a reconstruction of Islamic rationality grounded in tawhid and spirituality. The study’s main limitation lies in its reliance on textual analysis without empirical validation of how Tibi’s ideas operate in non-Western Muslim societies. Practically, it recommends educational reform that integrates religious and modern sciences, promotes rational literacy, and fosters critical dialogue between Islamic tradition and global modernity. This research contributes to Islamic philosophy by emphasizing the synthesis between rationality and spirituality. Practically, it offers a conceptual framework for Islamic education and intellectual reform to engage constructively with modernity while maintaining ethical and theological integrity.